Influence of coal gangue-aeolian sand aggregate gradation on rheological properties and pipeline transportation characteristics of filling slurry - Bo Liu; Yaoping Zhang; Shixing Yang (Scientific Reports)
Abstract Uneven of filling aggregate gradation may cause transportation problems such as pipe blockage due to segregation and stratification of filling slurry. To study the influence of aggregate gradation on the conveying performance of filler slurry, aggregate gradation experiments were carried out, rheological tests on slurries with coal gangue/aeolian sand ratios (6:4, 5:5 and 4:6) showed that appropriately increasing the proportion of aeolian sand can improve particle gradation. Computational fluid dynamics (CFD) scheme was used to simulate the pipeline transportation characteristics of the slurry under the conditions of three sets each of coal gangue/aeolian sand ratios, slurry concentrations (72%,74% and 76%), and inlet velocities (1.15,1.24 and 1.33 m/s). The results show that the pipeline resistance loss is directly proportional to the slurry concentration and inlet velocity, and inversely proportional to the coal gangue/aeolian sand, which indicates that the proportion of aeolian sand should be reduced in filling project to reduce the pipeline transportation resistance.